Pembuktian Noodweer Excess pada Tindak Pidana Pembunuhan dalam Studi Putusan Nomor 272/PID/2020/PT PDG - Sakila Nur Azahra; Rugun Romaida Hutabarat (LPPM Universitas Ekasakti Padang, 2023)
Forced defense that goes beyond its limits is included in one of the reasons for abolition of a sentence because it protects oneself, honor and property accompanied by extreme mental shock based on reasons of forgiveness as explained in Article 49 paragraph (2) as happened in Decision Number 272 /PID/2020/PT PDG. The aim is to analyze how to prove noodweer excess in the crime of murder in the study of decision number 272/pid/2020/pt pdg. This writing uses normative or doctrinal legal research, because it uses information sources of norms. As experienced by the defendant Efendi Putra (Decision Number 272/PID/2020/PT PDG) carrying out a defense against himself due to a threat of crime carried out by Adek Firdaus, which Adek Firdaus carried out in the form of throwing a machete which he had hidden in the jacket he was wearing. suddenly so that the defendant carried out self-defense which unexpectedly crossed the line due to extreme mental shock which is a reason for expunging the crime within the excuse of forgiveness (Article 49 paragraph (2))